Orthogonal polynomials associated with related measures and Sobolev orthogonal polynomials - Berti, A. C.; Bracciali, Cleonice Fátima [UNESP]; Ranga, A. Sri [UNESP] (Springer Nature, 2003)
Connection between two sequences of orthogonal polynomials, where the associated measures are related to each other by a first degree polynomial multiplication (or division), are looked at. The results are applied to obtain information regarding Sobolev orthogonal polynomials associated with certain pairs of measures.
Keywords: Coherent pair of measures; Sobolev orthogonal polynomials